State estimator condition number analysis. - Ebrahimian, R.
This paper develops formulas for the condition number of the state estimation problem as a function of the different types and number of measurements. We present empirical results using the IEEE RTS-96 and IEEE 118 bus systems that validate the formulas
Keywords: IEEE 118 bus system; IEEE RTS-96 bus system; Injection measurements; Power flow measurements; Power systems; State estimator condition number analysis; Voltage flow